Занятость населения Украины в неформальном секторе экономики - Мимандусова, Г. (Социология: теория, методы, маркетинг, 2000)
In accordance with sociological research data, there were analyzed the main reasons due to which the population intends to be involved into unregulated economic spheres.There were discussed the specific structure of those employed in informal economic spheres and levels of such employment for various kinds of informal activity, the factors that prevented people from official registration of their business and economic behavior of the population employed in informal economic spheres.